Riding the Indian tiger : - Nobrega, William (J. Wiley & Sons, 2008)
India is poised to overtake China in 2007 as the world’s fastest growing economy and is becoming one of the largest economies globally. Direct foreign investment in India has increased dramatically over the past three years and the pace of activity continues to quicken as large private equity funds create new emerging market funds and corporations continue to look for new revenue growth. The middle class is expected to grow from 90 million individuals today to 351 million individuals by 2010, and the retail market is expected to grow from